The Implementation Of Audio Lingual Method In Teaching English At The Fourth Year Of SD N Bedoro 2 Sambungmacan-Sragen - Suryani, Ninik (2012)
This research aims at describing the implementation of teaching Audio Lingual Method in teaching English at the fourth year of SD N Bedoro 2 Sambungmacan- Sragen. The objectives of this research paper are to describe: (1) the implementation of Audio Lingual Method in teaching English especially at the fourth year of SD N Bedoro 2 Sambungmacan Sragen, (2) the problems faced by the teacher and the solution in teaching English using Audio Lingual Method. The type of this research is descriptive qualitative research. The subject of this research is English teacher and the fourth grade students of SD N Bedoro 2 Sambungmacan. The object of this research is teaching-learning process of English by using Audio Lingual Method. The writer uses descriptive method as method of collecting data in this study by employing observation, interview, and document. The writer gets the data of this research from field note, observation, and interview. The result of the analysis shows that the goals of teaching English by using Audio Lingual Method are the students more active in the word and sentences repetition drilling. This technique was appropriate to the young learner because it made the students easier to memorizing new words. The teacher faces several problems in teaching English by using Audio Lingual Method; namely: limited time, motivation of the students, and different capabilities of the students.The solution of the problem in teaching English using Audio Lingual Method are as follows; discipline, teacher gives more support and motivation to the students, and the teacher should make the lesson interesting.